Pengaruh Strategi Pemasaran Terhadap Keputusan Pembelian Konsumen Pada Tempat Foto Copy Partidol Kota Sorong - Susan Alicia Darado; Meysa Ida Mangerongkonda; Ronaldo J P Siahaan (Jurnal Riset dan Inovasi Manajemen, 2023)
The purpose of this study was to determine the influence of marketing strategies on consumer purchasing decisions in the Partidol Photocopying Business in Sorong City. This study used a quantitative method with data collection techniques used by distributing questionnaires to consumers as many as 107 people. The processing of the data used in this study is the validity test, reliability test, classic assumption test, normality test, heteroscedasticity test, simple linear regression analysis, t test, and analysis of the coefficient of determination. The tools used are Microsoft Excel and SPSS software. The research results obtained were that there was no partial effect where the researchers compared the t-count values with significant values, so that the results obtained were that marketing strategies did not affect consumer purchasing decisions at the Sorong City Partidol Photo Copy.